Dakwah Digital dan Pembentukan Identitas: Studi Netnografi Gerakan Hijrah SHIFT di Media Sosial - Pipir Romadi S.Kom.I., M.M (KOMUNIDA : Media Komunikasi dan Dakwah, 2026)
This study aims to analyze the digital preaching practices of the SHIFT hijrah community on social media and to examine how digital interactions shape religious communication patterns and the religious identity of community members. The focus of this research includes the forms of preaching content, patterns of audience engagement, and the processes of meaning-making in digital religious spaces. The study employs a qualitative method using a netnographic approach. Data were collected through non-participant observation of the SHIFT accounts on Instagram, TikTok, and YouTube. The data include various preaching posts, captions, user comments, and visual elements observed during the research period. Data analysis was conducted using thematic analysis techniques through data reduction, categorization, and interpretation of digital religious interaction patterns. The findings indicate that SHIFT’s digital preaching functions not only as a medium for delivering religious messages but also as an interactive social space. Audience engagement is built through motivational content, hijrah storytelling, the use of hashtags such as #1MinuteBoosterStories, and short video formats. High levels of interaction in the form of likes, comments, and shares indicate a process of social validation that strengthens emotional attachment and religious identity among community members. In addition, social media algorithms also contribute to expanding content reach by promoting posts with high engagement. This study highlights that social media plays an important role in the transformation of contemporary Islamic preaching, particularly in building participatory, interactive, and network-based religious communities